2016
DOI: 10.3389/fpsyg.2016.00138
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Disambiguation in Verb Learning: Evidence from the Conjoined-Subject Intransitive Frame in English and Mandarin Chinese

Abstract: When presented with a novel verb in a transitive frame (X is Ving Y), young children typically select a causative event referent, rather than one in which agents engage in parallel, non-causative synchronous events. However, when presented with a conjoined-subject intransitive frame (X and Y are Ving), participants (even adults, as we show) are at chance. Although in some instances, children older than three can obtain above-chance-level performance, these experiments still appear to rely upon a within-experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…Thus, we decided to also test an older group of participants (i.e., children older than 3 years of age) for whom we expected this ability would be present. Although there is no evidence in the literature showing that 3-to-4-year-olds would be able to exploit function words in real-time to determine the syntactic category of novel words and infer their meanings, there is at least evidence that 3-to-5-year-olds can succeed in tasks where they needed to discover the meaning of novel verbs while watching dynamic scenes at the screen (e.g., Imai et al, 2008; Nappa et al, 2009; Arunachalam et al, 2016) and they also succeed to learn novel word meanings after have heard only three occurrences of a novel word in informative linguistic contexts (e.g., Imai et al, 2005, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we decided to also test an older group of participants (i.e., children older than 3 years of age) for whom we expected this ability would be present. Although there is no evidence in the literature showing that 3-to-4-year-olds would be able to exploit function words in real-time to determine the syntactic category of novel words and infer their meanings, there is at least evidence that 3-to-5-year-olds can succeed in tasks where they needed to discover the meaning of novel verbs while watching dynamic scenes at the screen (e.g., Imai et al, 2008; Nappa et al, 2009; Arunachalam et al, 2016) and they also succeed to learn novel word meanings after have heard only three occurrences of a novel word in informative linguistic contexts (e.g., Imai et al, 2005, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Going further, several studies demonstrated that 2-year-olds can use syntax even more specifically, not only to identify that a novel word is a verb or a noun but also to infer what kind of event a given verb is referring to depending on the syntactic structure in which it appears. For instance, 2-year-olds interpret a novel verb such as “blicking” as referring specifically to a causal event between two participants when they listen to transitive sentences such as “She is blicking the baby,” but they do not build the same interpretation about that novel verb when they listen to intransitive sentences such as “She is blicking” (e.g., Yuan and Fisher, 2009; Arunachalam and Waxman, 2010; Scott and Fisher, 2012; Yuan et al, 2012; Dautriche et al, 2014; Messenger et al, 2015; Arunachalam et al, 2016; Suzuki and Kobayashi, 2017; Arunachalam and Dennis, 2018). Moreover, recent studies demonstrated that 19- and 24-month-olds exposed to sentences like “The vep is crying” inferred that “vep” referred to an animate entity (i.e., a novel animal), because it appeared in the subject position of a familiar verb that requires an animate agent; in contrast, participants who were exposed to sentences like “The vep is right here” showed no preference for an animate entity at test (Ferguson et al, 2014, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two children's scores on the Social Communication Questionnaire (SCQ; Rutter, Bailey, & Lord, 2003) were both above the cutoff of 15 (21 and 23), indicating that they met criterion; however, the SCQ was designed 1 Although we generally think it is ideal to use within-subject manipulations with clinical populations to permit detailed analyses of individual differences, we adopt the standard between-subjects design for this paradigm because of concerns that exposure to one condition would affect performance in the other. See our discussion of the potential impact of this design choice in Arunachalam, Syrett, and Chen (2016).…”
Section: Methods Participantsmentioning
confidence: 99%
“…We instead follow on numerous prior studies with typically developing children (beginning with Naigles, 1990), which used a between-subjects design and randomly assigned children to either a transitive condition or an intransitive condition (e.g., "The boy and the girl are mooping"). Because the intransitive sentence can refer to either a causative event or synchronous events (Arunachalam, Syrett, & Chen, 2016;Naigles & Kako, 1993), the intransitive condition serves as a control against which we compare performance in the transitive condition. 1 Shulman and Guberman (2007) included both transitive and intransitive conditions, but their study involved children who were quite a bit older (mean age = 5;7), and furthermore, they were acquiring Hebrew, whose syntactic properties differ from English in important ways, making comparison difficult.…”
mentioning
confidence: 99%